TANTANGAN TERHADAP EKSISTENSI NEGARA BANGSA INDONESIA DAN PEMAKNAAN KEMBALI NASIONALISME - Sugiyarto Sugiyarto (Faculty of Humanities, Diponegoro University, 2012)
Concrete experience in the past has made the term nationalism very important in constructing Indonesian identity, as a unifying factor of diverse communities throughout the archipelago, not merely an academic, theoretical concept. The nation state ideology found its final expression in Pancasila and the 1945 Constitution. But even since the birth of this Republic, ideological conflicts never stop happening. And unfortunately, since the new order regime, the meaning of nationalism keeps on being distorted, manipulated, and then decreases into phenomena of separating actions from many local communities, showing their refusal to continue to be a part of Indonesia nation state. There is a need to reinterpret nationalism through Pancasila values in the current global era. Keywords: nationalism, Pancasila, globalization